Climate projection for the period 2006-2075 for the Jauja Valley, simulated by the intercomparison of coupled models CSIRO Mk 3.0, MIROC-ESM and CNRM phase 5 (CMIP5) - García López, Yvan (2022)
The climatic data for the Jauja valley, Junín region, central highlands of Peru for the xxi century were evaluated, as simulated by the climatic models used in phase 5 by the Intercomparison of coupled models (CMP5). The models used were three (03): CSIRO Mk 3.6, MIROC ESM and CNRM CM5, respectively, at a spatial resolution of 1,875 × 1.86°, 2,81 × 1.87° and 1,41 × 1,40°, built by observed meteorological data in the Jauja valley during the 1975-2005 period, using the IPCC RCP2.6 and 8.5 scenario. The present work is to provide local climate projections for this area, generating a first future climate database for the region, as a decision-making tool for farmers and other users of the basin. The climatic projections show a significant warming from 2,0 degrees of temperature for the RCP2.6 scenario to 3,5 degrees of temperature for the RCP8.5 scenario expected in the entire evaluated area of the Jauja valley for the next fifty years, together with a decrease in precipitation. Precipitation projections are dependent on horizontal resolution, suggesting the need for additional simulations at higher resolution, especially for adequate representation of extreme weather events.